The Mullerian Reconnaissance - Cutaneous Ciliated Cyst - Anubha, Bajaj (Journal of Clinical and Diagnostic Pathology, 2019)
Cutaneous ciliated cyst is cogitated as a benign,  exceptional lesion  and can be additionally termed as cutaneous Mullerian cyst or a cystadenoma.  Cutaneous ciliated cyst was initially described by Da Hess in 1890 and further elucidated in 1978 by  Farmer and Helwig as a cyst predominantly  occurring  in young  females within the second and third decades of life 12. Cutaneous ciliated cyst is a lesion of post- pubertal females, can appear in the reproductive phase and frequently  enlarges during menstruation or pregnancy due to hormonal effects. Cutaneous ciliated cyst  is commonly situated within deep-seated dermal or  subcutaneous tissue of the upper extremities  and perianal region. Cutaneous ciliated cyst delineates as Mullerian derivation in females and a distinct,  foetal eccrine duct origin in males 12.
Keywords: Cutaneous ciliated cyst; cystadenoma; foetal eccrine